Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10681-012-0648-6
|View full text |Cite
|
Sign up to set email alerts
|

GGE biplot analysis to evaluate genotype, environment and their interactions in sorghum multi-location data

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is a very important crop in the arid and semi-arid tropics of India and African subcontinent. In the process of release of new cultivars using multi-location data major emphasis is being given on the superiority of the new cultivars over the ruling cultivars, while very less importance is being given on the genotype 9 environment interaction (GEI). In the present study, performance of ten Indian hybrids over 12 locations across the rainy seasons of 2008 and 2009 was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
127
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 37 publications
19
127
1
1
Order By: Relevance
“…For the early and medium groups, this approach provided three of the more stable clusters and for the late-maturity genotypes, four stable environmental strata were produced (Table 4). These results agree with those obtained by other authors, in environmental stratification studies for sorghum grain yield (Rakshit et al, 2012), barley (Mohammadi et al, 2009;Mortazavian et al, 2014), and maize (Oyekunle et al, 2017). The AMMI1 model offers greater repeatability of the clusters, concerning more parameterized AMMI models, which incorporate more axes of the GxE interaction (Gauch, 1990(Gauch, , 1992Ebdon and Gauch, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…For the early and medium groups, this approach provided three of the more stable clusters and for the late-maturity genotypes, four stable environmental strata were produced (Table 4). These results agree with those obtained by other authors, in environmental stratification studies for sorghum grain yield (Rakshit et al, 2012), barley (Mohammadi et al, 2009;Mortazavian et al, 2014), and maize (Oyekunle et al, 2017). The AMMI1 model offers greater repeatability of the clusters, concerning more parameterized AMMI models, which incorporate more axes of the GxE interaction (Gauch, 1990(Gauch, , 1992Ebdon and Gauch, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Based on this points, Munaro et al (2014), evaluating different spring wheat cultivars for 3 years at 12 test locations in Brazil, identified superior cultivars and advanced lines for cultivars release. Similar results were obtained by Rakshit et al (2012) using sorghum hybrids, SotoCerda et al (2014) with linseed genotypes, Rolins et al (2013) and von Korf (2008) …”
Section: Introductionsupporting
confidence: 81%
“…Rakshit et al (2012) and Amiri et al(2015) all of them identified verities suitable for a defined production system.…”
Section: Genotypic Performance Of Yield and Yield Related Traitsmentioning
confidence: 99%